240 STANDARDISING POST-FALL MEDICAL REVIEWS FOR HOSPITAL INPATIENTS. (25th October 2022) - Daly, S; Gibbons, C; Callaly, E; Gaynor, E
Abstract: Background: Falls are the most common adverse incident of inpatients in Irish hospitals. 6% of inpatient falls cause serious injury. Older inpatients have the highest risk of falling and the highest risk of injury. The post-fall medical review is critical to assess why a patient fell, did the fall cause injury and for the introduction of measures to prevent future falls. We assessed the quality of the post fall reviews in a large hospital. We then introduced a standardised post-fall medical review pro forma and reassessed the quality of the reviews. Methods: We reviewed 18 charts of patients that fell in hospital and assessed the documentation of the post fall review in terms of the inclusion of key elements such as patient identifiers, history, examination, injury management and future falls prevention. We then introduced a post-fall standardised pro-forma on five wards in the hospital and following this assessed 19 charts of patients who had fallen looking at the same key elements of the post fall review. We compared the quality of the post-fall review before and after the introduction of the pro forma. Results: The post-falls medical review pro forma improved the quality of the post fall medical review. Hip Trauma: 11.1% of doctors asked about hip strike prior to proforma versus 100% who asked with the proforma. Joint examination: 50% assessed this prior to the proforma versus 100% with the pro-forma. Other aspects of the review that improved included head-strike assessment (89% versus 100%), loss of consciousness history (61% versus 95%), medication reviewed (22% versus 68%) and vital signs assessed (67% versus 95%). Conclusion: The introduction of a standardised post fall review pro forma improves the quality of this important medical review. It is a useful aid for doctors and provides a framework to follow when reviewing the patient.